2015
DOI: 10.1111/acer.12785
|View full text |Cite
|
Sign up to set email alerts
|

DrosophilaandCaenorhabditis elegansas Discovery Platforms for Genes Involved in Human Alcohol Use Disorder

Abstract: Background Despite the profound clinical significance and strong heritability of alcohol use disorder (AUD), we do not yet have a comprehensive understanding of the naturally occurring genetic variance within the human genome that drives its development. This lack of understanding is likely to be due in part to the large phenotypic and genetic heterogeneities that underlie human AUD. As a complement to genetic studies in humans, many laboratories are using the invertebrate model organisms (iMOs) Drosophila mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 179 publications
1
64
0
Order By: Relevance
“…Our results highlight the circadian clock as a candidate mediating age-related increases in alcohol toxicity and demonstrates that disruption of circadian function exacerbates alcohol toxicity, similar to aging phenotypes. Drosophila has proven a valuable model for studies of aging (Giebultowicz and Long, 2015, He and Jasper, 2014, Jones and Grotewiel, 2011), the circadian clock (Allada and Chung, 2010) and alcohol neurobiology (Grotewiel and Bettinger, 2015, Guarnieri and Heberlein, 2003) and the current study demonstrates the value of Drosophila as a practical model for investigating the interplay among these factors. This research lays the groundwork for future studies investigating the cellular and physiological mechanisms through which the circadian clock and aging influence alcohol-induced toxicity.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our results highlight the circadian clock as a candidate mediating age-related increases in alcohol toxicity and demonstrates that disruption of circadian function exacerbates alcohol toxicity, similar to aging phenotypes. Drosophila has proven a valuable model for studies of aging (Giebultowicz and Long, 2015, He and Jasper, 2014, Jones and Grotewiel, 2011), the circadian clock (Allada and Chung, 2010) and alcohol neurobiology (Grotewiel and Bettinger, 2015, Guarnieri and Heberlein, 2003) and the current study demonstrates the value of Drosophila as a practical model for investigating the interplay among these factors. This research lays the groundwork for future studies investigating the cellular and physiological mechanisms through which the circadian clock and aging influence alcohol-induced toxicity.…”
Section: Discussionmentioning
confidence: 70%
“…With conserved signaling pathways and clear parallels to mammalian physiology, Drosophila also presents a suitable model for dissecting molecular and neural interactions underlying alcohol sensitivity (Grotewiel and Bettinger, 2015, Guarnieri and Heberlein, 2003, Rodan and Rothenfluh, 2010). Stereotypical alcohol behaviors are highly conserved across species (Guarnieri and Heberlein, 2003, Rodan and Rothenfluh, 2010, Wolf et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, EtOH is the best-studied drug of abuse in C. elegans behavioral models, and genes affecting alcohol-associated behavior in worms have been linked to polymorphisms in orthologous genes in humans with alcohol-related sensitivity and/or disorders. 40 In general, these genes fall into categories related to (1) alcohol metabolism (i.e., alh-6 and alh-13), (2) neurotransmitter/modulator function including acetylcholine (unc-63), monoamines (cat-1), dopamine (dop-4 and cat-2), serotonin (tph-1), GABA (unc-25), neuropeptide Y (npr-1), (3) cation channels (slo-1, nca-1, and nca-2), and (4) chromatin remodeling complexes (swsn-4 and swsn-9). These data suggest that a number of orthologous neurobiologic systems and molecular mediators of EtOH effects in humans are present and also involved in behavioral responses to EtOH in C. elegans .…”
Section: Discussionmentioning
confidence: 99%
“…39 To date, at least 50 genes have been identified that influence EtOH-associated behaviors in C. elegans , and several orthologs of these genes have been implicated in alcohol use disorders in humans. 40 As with vertebrates, dopamine systems appear to play a role in EtOH-induced behavioral effects in C. elegans . EtOH induces state-dependent learning in C. elegans that is absent in animals with functional mutations in the vesicular monoamine transporter (cat-1) or tyrosine hydroxylase (cat-2).…”
Section: Drugs Of Abusementioning
confidence: 99%
“…Upon repeated exposures, flies develop tolerance (Scholz et al, 2000) and preference for alcohol consumption (Devineni and Heberlein, 2009; Peru y Colón de Portugal et al, 2014). Many of the genes regulating ethanol responses in Drosophila are conserved in mammals (Grotewiel and Bettinger, 2015), and a number of genes have been shown to affect alcohol responses in both flies and humans (Gonzalez et al, 2017; Ojelade et al, 2015; Schumann et al, 2016). Histone demethylase genes are also conserved between mammals and Drosophila , with the fly’s genome encoding 13 jumonji C domain-containing demethylases (JmjC-KDMs).…”
Section: Introductionmentioning
confidence: 99%